A sombra de Friedrich Engels: pela reabilitação do pensamento de Karl Marx - Silva, Vladmir Luis Da [UNIFESP] (2019)
The present work has as main objective the research of “Marxism” as it was ideated by Friedrich Engels (1820-1895) between the years 1859 and 1895 and, whithin this theoretical system, the research of the specificity of the sphere of human sociability. We also design here the comprehension of the real significance of his political position in his final days. The accomplishment of such work will be done through internal analysis of Engels’ texts. In a relatively little known review, Engels starts the definition of the configuration of Marxism with the assertion that Marx’s working method is historical and logical. Consequently, the Marxian criticism of political economy would have a simultaneously historical and logical disposition. In line with the cientific spirit of mid-nineteenth century, Engels tried to enlarge the new theory to the area of the natural sciences. The autor was trying to lay the foundation of the existence of universal dialectical laws in the areas of nature, history and human thought, thus proclaiming the end of philosophy as a particular science of synthesis. One of Engels’ main sources in the accomplishment of this work of expansion was Hegel’s work. However, Engels supposes to be following closely the steps of his intellectual partner and implies that his work and that of his friend constitute an unity, even though composed by sistematic division of labor. In the final period of his life, the autor tried to explain to the young militants of the European left the main features of the theory under development, now named “historical materialism”. Lastly, Engels worked in a brief but controversial analysis of the prospects for the socialist revolution in the scenario of the second half of the nineteenth century. The text at issue has been edited by opportunist leaders of the German Social Democratic Party (SPD) and used in favour of a revisionist thread, which tended towards the defense of reformism.